2018
DOI: 10.1002/pchj.200
|View full text |Cite
|
Sign up to set email alerts
|

Body image attitude among Chinese college students

Abstract: The present study aimed to examine body image attitude in Chinese college students and related psychological consequences. A silhouette-matching test was administered to 425 college students in mainland China. Self-esteem, negative emotions, subjective well-being, and eating-disorder-related weight-controlling behaviors were also measured. Only 12.9% of the participants were satisfied with their figure and the extent of body image dissatisfaction was comparable for both sexes. The majority of the female partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
38
3
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 53 publications
(63 reference statements)
6
38
3
3
Order By: Relevance
“…6,7,9,11,[29][30][31][32] but we followed the original proposal, with its seven correlated subscales. 4,8,33 With regard to the correlations between the BIBCI subscales, the majority were significant, corroborating results presented by 34,35 and revealing that this population strongly values the body. Moreover, most of the students presented very low use of strategies for body change.…”
Section: Introductionsupporting
confidence: 77%
“…6,7,9,11,[29][30][31][32] but we followed the original proposal, with its seven correlated subscales. 4,8,33 With regard to the correlations between the BIBCI subscales, the majority were significant, corroborating results presented by 34,35 and revealing that this population strongly values the body. Moreover, most of the students presented very low use of strategies for body change.…”
Section: Introductionsupporting
confidence: 77%
“…Furthermore, they are known to predict lack of psychological wellbeing and mental health (Argyle, 2013;Cheng & Furnham, 2002). Previous studies have found that higher depressive symptoms, lower self-esteem, higher loneliness, and elevated social anxiety to be highly associated with both childhood emotional trauma (Finzi-Dottan & Karu, 2006;Heim et al, 2009;Norton & Abbott, 2017;Runyan et al, 2002;Saleh et al, 2017) and body image dissatisfaction (Junne et al, 2016;Wang et al, 2018). Additionally, depressive symptoms, low self-esteem, loneliness, and high social anxiety have frequently been associated with IGD (Andreassen et al, 2016;Bargeron & Hormes, 2017;Beard & Wickham, 2016;Griffiths, Király, Pontes, & Demetrovics, 2015;Laconi et al, 2017;Lemmens, Valkenburg, & Gentile, 2015;Sioni et al, 2017).…”
Section: The Mediating Role Of Body Image Dissatisfactionmentioning
confidence: 99%
“…The findings may help us understand to what extent Chinese college students internalize the thin ideal. A previous survey in Beijing college students has indicated that 72.8% of women and 46.2% of men wished to have a smaller figure than their current one (Wang et al, ). The prevalence of overweight adults in China has increased from 11.7% in 1991 to 29.2% in 2009 (Gordon‐Larsen, Wang, & Popkin, ).…”
mentioning
confidence: 95%
“…While the interpretation of this observation is reasonable, it appears counterintuitive based on today's culture. First, many women with a normal BMI experience body image dissatisfaction (Wang et al, ; Zaccagni, Masotti, Donati, Mazzoni, & Gualdi‐Russo, ). Second, it seems that only women who are underweight are satisfied with their body shape (Kantanista, Król‐Zielińska, Borowiec, & Osiński, ; Neighbors & Sobal, ).…”
mentioning
confidence: 99%
See 1 more Smart Citation